blocking_semantics3_HoareLogic_assert_rule_ext_1.v 23.7 KB
Newer Older
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
(* This file is generated by Why3's Coq driver *)
(* Beware! Only edit allowed sections below    *)
Require Import BuiltIn.
Require BuiltIn.
Require int.Int.
Require int.MinMax.

(* Why3 assumption *)
Inductive list (a:Type) {a_WT:WhyType a} :=
  | Nil : list a
  | Cons : a -> (list a) -> list a.
Axiom list_WhyType : forall (a:Type) {a_WT:WhyType a}, WhyType (list a).
Existing Instance list_WhyType.
Implicit Arguments Nil [[a] [a_WT]].
Implicit Arguments Cons [[a] [a_WT]].

Axiom map : forall (a:Type) {a_WT:WhyType a} (b:Type) {b_WT:WhyType b}, Type.
Parameter map_WhyType : forall (a:Type) {a_WT:WhyType a}
  (b:Type) {b_WT:WhyType b}, WhyType (map a b).
Existing Instance map_WhyType.

Parameter get: forall {a:Type} {a_WT:WhyType a} {b:Type} {b_WT:WhyType b},
  (map a b) -> a -> b.

Parameter set: forall {a:Type} {a_WT:WhyType a} {b:Type} {b_WT:WhyType b},
  (map a b) -> a -> b -> (map a b).

Axiom Select_eq : forall {a:Type} {a_WT:WhyType a} {b:Type} {b_WT:WhyType b},
  forall (m:(map a b)), forall (a1:a) (a2:a), forall (b1:b), (a1 = a2) ->
  ((get (set m a1 b1) a2) = b1).

Axiom Select_neq : forall {a:Type} {a_WT:WhyType a}
  {b:Type} {b_WT:WhyType b}, forall (m:(map a b)), forall (a1:a) (a2:a),
  forall (b1:b), (~ (a1 = a2)) -> ((get (set m a1 b1) a2) = (get m a2)).

Parameter const: forall {a:Type} {a_WT:WhyType a} {b:Type} {b_WT:WhyType b},
  b -> (map a b).

Axiom Const : forall {a:Type} {a_WT:WhyType a} {b:Type} {b_WT:WhyType b},
  forall (b1:b) (a1:a), ((get (const b1:(map a b)) a1) = b1).

(* Why3 assumption *)
Inductive datatype  :=
  | TYunit : datatype 
  | TYint : datatype 
  | TYbool : datatype .
Axiom datatype_WhyType : WhyType datatype.
Existing Instance datatype_WhyType.

(* Why3 assumption *)
Inductive value  :=
  | Vvoid : value 
  | Vint : Z -> value 
  | Vbool : bool -> value .
Axiom value_WhyType : WhyType value.
Existing Instance value_WhyType.

(* Why3 assumption *)
Inductive operator  :=
  | Oplus : operator 
  | Ominus : operator 
  | Omult : operator 
  | Ole : operator .
Axiom operator_WhyType : WhyType operator.
Existing Instance operator_WhyType.

Axiom mident : Type.
Parameter mident_WhyType : WhyType mident.
Existing Instance mident_WhyType.

(* Why3 assumption *)
Inductive ident  :=
  | mk_ident : Z -> ident .
Axiom ident_WhyType : WhyType ident.
Existing Instance ident_WhyType.

(* Why3 assumption *)
Definition ident_index(v:ident): Z := match v with
  | (mk_ident x) => x
  end.

(* Why3 assumption *)
Inductive term_node  :=
  | Tvalue : value -> term_node 
  | Tvar : ident -> term_node 
  | Tderef : mident -> term_node 
  | Tbin : term -> operator -> term -> term_node 
  with term  :=
  | mk_term : term_node -> Z -> term .
Axiom term_WhyType : WhyType term.
Existing Instance term_WhyType.

Axiom term_node_WhyType : WhyType term_node.
Existing Instance term_node_WhyType.

(* Why3 assumption *)
Definition term_maxvar(v:term): Z := match v with
  | (mk_term x x1) => x1
  end.

(* Why3 assumption *)
Definition term_node1(v:term): term_node :=
  match v with
  | (mk_term x x1) => x
  end.

(* Why3 assumption *)
Fixpoint var_occurs_in_term(x:ident) (t:term) {struct t}: Prop :=
  match t with
  | (mk_term (Tvalue _) _) => False
  | (mk_term (Tvar i) _) => (x = i)
  | (mk_term (Tderef _) _) => False
  | (mk_term (Tbin t1 _ t2) _) => (var_occurs_in_term x t1) \/
      (var_occurs_in_term x t2)
  end.

(* Why3 assumption *)
Definition term_inv(t:term): Prop := forall (x:ident), (var_occurs_in_term x
  t) -> ((ident_index x) <= (term_maxvar t))%Z.

(* Why3 assumption *)
Definition mk_tvalue(v:value): term := (mk_term (Tvalue v) (-1%Z)%Z).

Axiom mk_tvalue_inv : forall (v:value), (term_inv (mk_tvalue v)).

(* Why3 assumption *)
Definition mk_tvar(i:ident): term := (mk_term (Tvar i) (ident_index i)).

Axiom mk_tvar_inv : forall (i:ident), (term_inv (mk_tvar i)).

(* Why3 assumption *)
Definition mk_tderef(r:mident): term := (mk_term (Tderef r) (-1%Z)%Z).

Axiom mk_tderef_inv : forall (r:mident), (term_inv (mk_tderef r)).

(* Why3 assumption *)
Definition mk_tbin(t1:term) (o:operator) (t2:term): term := (mk_term (Tbin t1
  o t2) (Zmax (term_maxvar t1) (term_maxvar t2))).

Axiom mk_tbin_inv : forall (t1:term) (t2:term) (o:operator),
  ((term_inv t1) /\ (term_inv t2)) -> (term_inv (mk_tbin t1 o t2)).

(* Why3 assumption *)
Inductive fmla  :=
  | Fterm : term -> fmla 
  | Fand : fmla -> fmla -> fmla 
  | Fnot : fmla -> fmla 
  | Fimplies : fmla -> fmla -> fmla 
  | Flet : ident -> term -> fmla -> fmla 
  | Fforall : ident -> datatype -> fmla -> fmla .
Axiom fmla_WhyType : WhyType fmla.
Existing Instance fmla_WhyType.

(* Why3 assumption *)
Inductive stmt  :=
  | Sskip : stmt 
  | Sassign : mident -> term -> stmt 
  | Sseq : stmt -> stmt -> stmt 
  | Sif : term -> stmt -> stmt -> stmt 
  | Sassert : fmla -> stmt 
  | Swhile : term -> fmla -> stmt -> stmt .
Axiom stmt_WhyType : WhyType stmt.
Existing Instance stmt_WhyType.

(* Why3 assumption *)
Definition type_value(v:value): datatype :=
  match v with
  | Vvoid => TYunit
  | (Vint int) => TYint
  | (Vbool bool1) => TYbool
  end.

(* Why3 assumption *)
Inductive type_operator : operator -> datatype -> datatype
  -> datatype -> Prop :=
  | Type_plus : (type_operator Oplus TYint TYint TYint)
  | Type_minus : (type_operator Ominus TYint TYint TYint)
  | Type_mult : (type_operator Omult TYint TYint TYint)
  | Type_le : (type_operator Ole TYint TYint TYbool).

(* Why3 assumption *)
Definition type_stack  := (list (ident* datatype)%type).

Parameter get_vartype: ident -> (list (ident* datatype)%type) -> datatype.

Axiom get_vartype_def : forall (i:ident) (pi:(list (ident* datatype)%type)),
  match pi with
  | Nil => ((get_vartype i pi) = TYunit)
  | (Cons (x, ty) r) => ((x = i) -> ((get_vartype i pi) = ty)) /\
      ((~ (x = i)) -> ((get_vartype i pi) = (get_vartype i r)))
  end.

(* Why3 assumption *)
Definition type_env  := (map mident datatype).

(* Why3 assumption *)
Inductive type_term : (map mident datatype) -> (list (ident* datatype)%type)
  -> term -> datatype -> Prop :=
  | Type_value : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (v:value) (m:Z), (type_term sigma pi
      (mk_term (Tvalue v) m) (type_value v))
  | Type_var : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (v:ident) (m:Z) (ty:datatype), ((get_vartype v
      pi) = ty) -> (type_term sigma pi (mk_term (Tvar v) m) ty)
  | Type_deref : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (v:mident) (m:Z) (ty:datatype), ((get sigma
      v) = ty) -> (type_term sigma pi (mk_term (Tderef v) m) ty)
  | Type_bin : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (t1:term) (t2:term) (op:operator) (m:Z) (ty1:datatype)
      (ty2:datatype) (ty:datatype), (type_term sigma pi t1 ty1) ->
      ((type_term sigma pi t2 ty2) -> ((type_operator op ty1 ty2 ty) ->
      (type_term sigma pi (mk_term (Tbin t1 op t2) m) ty))).

(* Why3 assumption *)
Inductive type_fmla : (map mident datatype) -> (list (ident* datatype)%type)
  -> fmla -> Prop :=
  | Type_term : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (t:term), (type_term sigma pi t TYbool) ->
      (type_fmla sigma pi (Fterm t))
  | Type_conj : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (f1:fmla) (f2:fmla), (type_fmla sigma pi f1) ->
      ((type_fmla sigma pi f2) -> (type_fmla sigma pi (Fand f1 f2)))
  | Type_neg : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (f:fmla), (type_fmla sigma pi f) -> (type_fmla sigma
      pi (Fnot f))
  | Type_implies : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (f1:fmla) (f2:fmla), (type_fmla sigma pi f1) ->
      ((type_fmla sigma pi f2) -> (type_fmla sigma pi (Fimplies f1 f2)))
  | Type_let : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (x:ident) (t:term) (f:fmla) (ty:datatype),
      (type_term sigma pi t ty) -> ((type_fmla sigma (Cons (x, ty) pi) f) ->
      (type_fmla sigma pi (Flet x t f)))
  | Type_forall1 : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (x:ident) (f:fmla), (type_fmla sigma (Cons (x, TYint)
      pi) f) -> (type_fmla sigma pi (Fforall x TYint f))
  | Type_forall2 : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (x:ident) (f:fmla), (type_fmla sigma (Cons (x, TYbool)
      pi) f) -> (type_fmla sigma pi (Fforall x TYbool f))
  | Type_forall3 : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (x:ident) (f:fmla), (type_fmla sigma (Cons (x, TYunit)
      pi) f) -> (type_fmla sigma pi (Fforall x TYunit f)).

(* Why3 assumption *)
Inductive type_stmt : (map mident datatype) -> (list (ident* datatype)%type)
  -> stmt -> Prop :=
  | Type_skip : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)), (type_stmt sigma pi Sskip)
  | Type_seq : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (s1:stmt) (s2:stmt), (type_stmt sigma pi s1) ->
      ((type_stmt sigma pi s2) -> (type_stmt sigma pi (Sseq s1 s2)))
  | Type_assigns : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (x:mident) (t:term) (ty:datatype), ((get sigma
      x) = ty) -> ((type_term sigma pi t ty) -> (type_stmt sigma pi
      (Sassign x t)))
  | Type_if : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (t:term) (s1:stmt) (s2:stmt), (type_term sigma pi t
      TYbool) -> ((type_stmt sigma pi s1) -> ((type_stmt sigma pi s2) ->
      (type_stmt sigma pi (Sif t s1 s2))))
  | Type_assert : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (p:fmla), (type_fmla sigma pi p) -> (type_stmt sigma
      pi (Sassert p))
  | Type_while : forall (sigma:(map mident datatype)) (pi:(list (ident*
      datatype)%type)) (guard:term) (body:stmt) (inv:fmla), (type_fmla sigma
      pi inv) -> ((type_term sigma pi guard TYbool) -> ((type_stmt sigma pi
      body) -> (type_stmt sigma pi (Swhile guard inv body)))).

(* Why3 assumption *)
Definition env  := (map mident value).

(* Why3 assumption *)
Definition stack  := (list (ident* value)%type).

Parameter get_stack: ident -> (list (ident* value)%type) -> value.

Axiom get_stack_def : forall (i:ident) (pi:(list (ident* value)%type)),
  match pi with
  | Nil => ((get_stack i pi) = Vvoid)
  | (Cons (x, v) r) => ((x = i) -> ((get_stack i pi) = v)) /\ ((~ (x = i)) ->
      ((get_stack i pi) = (get_stack i r)))
  end.

Axiom get_stack_eq : forall (x:ident) (v:value) (r:(list (ident*
  value)%type)), ((get_stack x (Cons (x, v) r)) = v).

Axiom get_stack_neq : forall (x:ident) (i:ident) (v:value) (r:(list (ident*
  value)%type)), (~ (x = i)) -> ((get_stack i (Cons (x, v) r)) = (get_stack i
  r)).

Parameter eval_bin: value -> operator -> value -> value.

Axiom eval_bin_def : forall (x:value) (op:operator) (y:value), match (x,
  y) with
  | ((Vint x1), (Vint y1)) =>
      match op with
      | Oplus => ((eval_bin x op y) = (Vint (x1 + y1)%Z))
      | Ominus => ((eval_bin x op y) = (Vint (x1 - y1)%Z))
      | Omult => ((eval_bin x op y) = (Vint (x1 * y1)%Z))
      | Ole => ((x1 <= y1)%Z -> ((eval_bin x op y) = (Vbool true))) /\
          ((~ (x1 <= y1)%Z) -> ((eval_bin x op y) = (Vbool false)))
      end
  | (_, _) => ((eval_bin x op y) = Vvoid)
  end.

(* Why3 assumption *)
Fixpoint eval_term(sigma:(map mident value)) (pi:(list (ident* value)%type))
  (t:term) {struct t}: value :=
  match t with
  | (mk_term (Tvalue v) _) => v
  | (mk_term (Tvar id) _) => (get_stack id pi)
  | (mk_term (Tderef id) _) => (get sigma id)
  | (mk_term (Tbin t1 op t2) _) => (eval_bin (eval_term sigma pi t1) op
      (eval_term sigma pi t2))
  end.

(* Why3 assumption *)
Fixpoint eval_fmla(sigma:(map mident value)) (pi:(list (ident* value)%type))
  (f:fmla) {struct f}: Prop :=
  match f with
  | (Fterm t) => ((eval_term sigma pi t) = (Vbool true))
  | (Fand f1 f2) => (eval_fmla sigma pi f1) /\ (eval_fmla sigma pi f2)
  | (Fnot f1) => ~ (eval_fmla sigma pi f1)
  | (Fimplies f1 f2) => (eval_fmla sigma pi f1) -> (eval_fmla sigma pi f2)
  | (Flet x t f1) => (eval_fmla sigma (Cons (x, (eval_term sigma pi t)) pi)
      f1)
  | (Fforall x TYint f1) => forall (n:Z), (eval_fmla sigma (Cons (x,
      (Vint n)) pi) f1)
  | (Fforall x TYbool f1) => forall (b:bool), (eval_fmla sigma (Cons (x,
      (Vbool b)) pi) f1)
  | (Fforall x TYunit f1) => (eval_fmla sigma (Cons (x, Vvoid) pi) f1)
  end.

Parameter msubst_term: term -> mident -> ident -> term.

Axiom msubst_term_def : forall (t:term) (r:mident) (v:ident),
  match t with
  | (mk_term ((Tvalue _)|(Tvar _)) _) => ((msubst_term t r v) = t)
  | (mk_term (Tderef x) _) => ((r = x) -> ((msubst_term t r
      v) = (mk_tvar v))) /\ ((~ (r = x)) -> ((msubst_term t r v) = t))
  | (mk_term (Tbin t1 op t2) _) => ((msubst_term t r
      v) = (mk_tbin (msubst_term t1 r v) op (msubst_term t2 r v)))
  end.

Parameter subst_term: term -> ident -> ident -> term.

Axiom subst_term_def : forall (t:term) (r:ident) (v:ident),
  match t with
  | (mk_term ((Tvalue _)|(Tderef _)) _) => ((subst_term t r v) = t)
  | (mk_term (Tvar x) _) => ((r = x) -> ((subst_term t r
      v) = (mk_tvar v))) /\ ((~ (r = x)) -> ((subst_term t r v) = t))
  | (mk_term (Tbin t1 op t2) _) => ((subst_term t r
      v) = (mk_tbin (subst_term t1 r v) op (subst_term t2 r v)))
  end.

(* Why3 assumption *)
Definition fresh_in_term(id:ident) (t:term): Prop :=
  ((term_maxvar t) < (ident_index id))%Z.

Axiom eval_msubst_term : forall (sigma:(map mident value)) (pi:(list (ident*
  value)%type)) (e:term) (x:mident) (v:ident), (fresh_in_term v e) ->
  ((eval_term sigma pi (msubst_term e x v)) = (eval_term (set sigma x
  (get_stack v pi)) pi e)).

Axiom eval_subst_term : forall (sigma:(map mident value)) (pi:(list (ident*
  value)%type)) (e:term) (x:ident) (v:ident), (fresh_in_term v e) ->
  ((eval_term sigma pi (subst_term e x v)) = (eval_term sigma (Cons (x,
  (get_stack v pi)) pi) e)).

Axiom eval_term_change_free : forall (t:term) (sigma:(map mident value))
  (pi:(list (ident* value)%type)) (id:ident) (v:value), (fresh_in_term id
  t) -> ((eval_term sigma (Cons (id, v) pi) t) = (eval_term sigma pi t)).

(* Why3 assumption *)
Fixpoint fresh_in_fmla(id:ident) (f:fmla) {struct f}: Prop :=
  match f with
  | (Fterm e) => (fresh_in_term id e)
  | ((Fand f1 f2)|(Fimplies f1 f2)) => (fresh_in_fmla id f1) /\
      (fresh_in_fmla id f2)
  | (Fnot f1) => (fresh_in_fmla id f1)
  | (Flet y t f1) => (~ (id = y)) /\ ((fresh_in_term id t) /\
      (fresh_in_fmla id f1))
  | (Fforall y ty f1) => (~ (id = y)) /\ (fresh_in_fmla id f1)
  end.

(* Why3 assumption *)
Fixpoint subst(f:fmla) (x:ident) (v:ident) {struct f}: fmla :=
  match f with
  | (Fterm e) => (Fterm (subst_term e x v))
  | (Fand f1 f2) => (Fand (subst f1 x v) (subst f2 x v))
  | (Fnot f1) => (Fnot (subst f1 x v))
  | (Fimplies f1 f2) => (Fimplies (subst f1 x v) (subst f2 x v))
  | (Flet y t f1) => (Flet y (subst_term t x v) (subst f1 x v))
  | (Fforall y ty f1) => (Fforall y ty (subst f1 x v))
  end.

(* Why3 assumption *)
Fixpoint msubst(f:fmla) (x:mident) (v:ident) {struct f}: fmla :=
  match f with
  | (Fterm e) => (Fterm (msubst_term e x v))
  | (Fand f1 f2) => (Fand (msubst f1 x v) (msubst f2 x v))
  | (Fnot f1) => (Fnot (msubst f1 x v))
  | (Fimplies f1 f2) => (Fimplies (msubst f1 x v) (msubst f2 x v))
  | (Flet y t f1) => (Flet y (msubst_term t x v) (msubst f1 x v))
  | (Fforall y ty f1) => (Fforall y ty (msubst f1 x v))
  end.

Axiom subst_fresh : forall (f:fmla) (x:ident) (v:ident), (fresh_in_fmla x
  f) -> ((subst f x v) = f).

Axiom let_subst : forall (t:term) (f:fmla) (x:ident) (id':ident) (id:mident),
  ((msubst (Flet x t f) id id') = (Flet x (msubst_term t id id') (msubst f id
  id'))).

Axiom eval_msubst : forall (f:fmla) (sigma:(map mident value)) (pi:(list
  (ident* value)%type)) (x:mident) (v:ident), (fresh_in_fmla v f) ->
  ((eval_fmla sigma pi (msubst f x v)) <-> (eval_fmla (set sigma x
  (get_stack v pi)) pi f)).

Axiom eval_subst : forall (f:fmla) (sigma:(map mident value)) (pi:(list
  (ident* value)%type)) (x:ident) (v:ident), (fresh_in_fmla v f) ->
  ((eval_fmla sigma pi (subst f x v)) <-> (eval_fmla sigma (Cons (x,
  (get_stack v pi)) pi) f)).

Axiom eval_swap : forall (f:fmla) (sigma:(map mident value)) (pi:(list
  (ident* value)%type)) (id1:ident) (id2:ident) (v1:value) (v2:value),
  (~ (id1 = id2)) -> ((eval_fmla sigma (Cons (id1, v1) (Cons (id2, v2) pi))
  f) <-> (eval_fmla sigma (Cons (id2, v2) (Cons (id1, v1) pi)) f)).

Axiom eval_same_var : forall (f:fmla) (sigma:(map mident value)) (pi:(list
  (ident* value)%type)) (id:ident) (v1:value) (v2:value), (eval_fmla sigma
  (Cons (id, v1) (Cons (id, v2) pi)) f) <-> (eval_fmla sigma (Cons (id, v1)
  pi) f).

Axiom eval_change_free : forall (f:fmla) (sigma:(map mident value)) (pi:(list
  (ident* value)%type)) (id:ident) (v:value), (fresh_in_fmla id f) ->
  ((eval_fmla sigma (Cons (id, v) pi) f) <-> (eval_fmla sigma pi f)).

(* Why3 assumption *)
Definition valid_fmla(p:fmla): Prop := forall (sigma:(map mident value))
  (pi:(list (ident* value)%type)), (eval_fmla sigma pi p).

Axiom let_equiv : forall (id:ident) (id':ident) (t:term) (f:fmla),
  forall (sigma:(map mident value)) (pi:(list (ident* value)%type)),
  (fresh_in_fmla id' f) -> ((eval_fmla sigma pi (Flet id' t (subst f id
  id'))) -> (eval_fmla sigma pi (Flet id t f))).

Axiom let_equiv2 : forall (id:ident) (id':ident) (t:term) (f:fmla),
  forall (sigma:(map mident value)) (pi:(list (ident* value)%type)),
  (fresh_in_fmla id' f) -> ((eval_fmla sigma pi (Flet id' t (subst f id
  id'))) -> (eval_fmla sigma pi (Flet id t f))).

Axiom let_implies : forall (id:ident) (t:term) (p:fmla) (q:fmla),
  (valid_fmla (Fimplies p q)) -> (valid_fmla (Fimplies (Flet id t p) (Flet id
  t q))).

(* Why3 assumption *)
Fixpoint fresh_in_stmt(id:ident) (s:stmt) {struct s}: Prop :=
  match s with
  | Sskip => True
  | (Sseq s1 s2) => (fresh_in_stmt id s1) /\ (fresh_in_stmt id s2)
  | (Sassign _ t) => (fresh_in_term id t)
  | (Sif t s1 s2) => (fresh_in_term id t) /\ ((fresh_in_stmt id s1) /\
      (fresh_in_stmt id s2))
  | (Sassert f) => (fresh_in_fmla id f)
  | (Swhile cond inv body) => (fresh_in_term id cond) /\ ((fresh_in_fmla id
      inv) /\ (fresh_in_stmt id body))
  end.

(* Why3 assumption *)
Inductive one_step : (map mident value) -> (list (ident* value)%type) -> stmt
  -> (map mident value) -> (list (ident* value)%type) -> stmt -> Prop :=
  | one_step_assign : forall (sigma:(map mident value)) (sigma':(map mident
      value)) (pi:(list (ident* value)%type)) (x:mident) (t:term),
      (sigma' = (set sigma x (eval_term sigma pi t))) -> (one_step sigma pi
      (Sassign x t) sigma' pi Sskip)
  | one_step_seq_noskip : forall (sigma:(map mident value)) (sigma':(map
      mident value)) (pi:(list (ident* value)%type)) (pi':(list (ident*
      value)%type)) (s1:stmt) (s1':stmt) (s2:stmt), (one_step sigma pi s1
      sigma' pi' s1') -> (one_step sigma pi (Sseq s1 s2) sigma' pi' (Sseq s1'
      s2))
  | one_step_seq_skip : forall (sigma:(map mident value)) (pi:(list (ident*
      value)%type)) (s:stmt), (one_step sigma pi (Sseq Sskip s) sigma pi s)
  | one_step_if_true : forall (sigma:(map mident value)) (pi:(list (ident*
      value)%type)) (t:term) (s1:stmt) (s2:stmt), ((eval_term sigma pi
      t) = (Vbool true)) -> (one_step sigma pi (Sif t s1 s2) sigma pi s1)
  | one_step_if_false : forall (sigma:(map mident value)) (pi:(list (ident*
      value)%type)) (t:term) (s1:stmt) (s2:stmt), ((eval_term sigma pi
      t) = (Vbool false)) -> (one_step sigma pi (Sif t s1 s2) sigma pi s2)
  | one_step_assert : forall (sigma:(map mident value)) (pi:(list (ident*
      value)%type)) (f:fmla), (eval_fmla sigma pi f) -> (one_step sigma pi
      (Sassert f) sigma pi Sskip)
  | one_step_while_true : forall (sigma:(map mident value)) (pi:(list (ident*
      value)%type)) (cond:term) (inv:fmla) (body:stmt), (eval_fmla sigma pi
      inv) -> (((eval_term sigma pi cond) = (Vbool true)) -> (one_step sigma
      pi (Swhile cond inv body) sigma pi (Sseq body (Swhile cond inv body))))
  | one_step_while_falsee : forall (sigma:(map mident value)) (pi:(list
      (ident* value)%type)) (cond:term) (inv:fmla) (body:stmt),
      (eval_fmla sigma pi inv) -> (((eval_term sigma pi
      cond) = (Vbool false)) -> (one_step sigma pi (Swhile cond inv body)
      sigma pi Sskip)).

(* Why3 assumption *)
Inductive many_steps : (map mident value) -> (list (ident* value)%type)
  -> stmt -> (map mident value) -> (list (ident* value)%type) -> stmt
  -> Z -> Prop :=
  | many_steps_refl : forall (sigma:(map mident value)) (pi:(list (ident*
      value)%type)) (s:stmt), (many_steps sigma pi s sigma pi s 0%Z)
  | many_steps_trans : forall (sigma1:(map mident value)) (sigma2:(map mident
      value)) (sigma3:(map mident value)) (pi1:(list (ident* value)%type))
      (pi2:(list (ident* value)%type)) (pi3:(list (ident* value)%type))
      (s1:stmt) (s2:stmt) (s3:stmt) (n:Z), (one_step sigma1 pi1 s1 sigma2 pi2
      s2) -> ((many_steps sigma2 pi2 s2 sigma3 pi3 s3 n) ->
      (many_steps sigma1 pi1 s1 sigma3 pi3 s3 (n + 1%Z)%Z)).

Axiom steps_non_neg : forall (sigma1:(map mident value)) (sigma2:(map mident
  value)) (pi1:(list (ident* value)%type)) (pi2:(list (ident* value)%type))
  (s1:stmt) (s2:stmt) (n:Z), (many_steps sigma1 pi1 s1 sigma2 pi2 s2 n) ->
  (0%Z <= n)%Z.

Axiom many_steps_seq : forall (sigma1:(map mident value)) (sigma3:(map mident
  value)) (pi1:(list (ident* value)%type)) (pi3:(list (ident* value)%type))
  (s1:stmt) (s2:stmt) (n:Z), (many_steps sigma1 pi1 (Sseq s1 s2) sigma3 pi3
  Sskip n) -> exists sigma2:(map mident value), exists pi2:(list (ident*
  value)%type), exists n1:Z, exists n2:Z, (many_steps sigma1 pi1 s1 sigma2
  pi2 Sskip n1) /\ ((many_steps sigma2 pi2 s2 sigma3 pi3 Sskip n2) /\
  (n = ((1%Z + n1)%Z + n2)%Z)).

Axiom one_step_change_free : forall (s:stmt) (s':stmt) (sigma:(map mident
  value)) (sigma':(map mident value)) (pi:(list (ident* value)%type))
  (pi':(list (ident* value)%type)) (id:ident) (v:value), (fresh_in_stmt id
  s) -> ((one_step sigma (Cons (id, v) pi) s sigma' pi' s') ->
  (one_step sigma pi s sigma' pi' s')).

(* Why3 assumption *)
Definition valid_triple(p:fmla) (s:stmt) (q:fmla): Prop := forall (sigma:(map
  mident value)) (pi:(list (ident* value)%type)), (eval_fmla sigma pi p) ->
  forall (sigma':(map mident value)) (pi':(list (ident* value)%type)) (n:Z),
  (many_steps sigma pi s sigma' pi' Sskip n) -> (eval_fmla sigma' pi' q).

(* Why3 assumption *)
Definition total_valid_triple(p:fmla) (s:stmt) (q:fmla): Prop :=
  forall (sigma:(map mident value)) (pi:(list (ident* value)%type)),
  (eval_fmla sigma pi p) -> exists sigma':(map mident value),
  exists pi':(list (ident* value)%type), exists n:Z, (many_steps sigma pi s
  sigma' pi' Sskip n) /\ (eval_fmla sigma' pi' q).

Axiom consequence_rule : forall (p:fmla) (p':fmla) (q:fmla) (q':fmla)
  (s:stmt), (valid_fmla (Fimplies p' p)) -> ((valid_triple p s q) ->
  ((valid_fmla (Fimplies q q')) -> (valid_triple p' s q'))).

Axiom skip_rule : forall (q:fmla), (valid_triple q Sskip q).

Axiom assign_rule : forall (p:fmla) (x:mident) (id:ident) (t:term),
  (fresh_in_fmla id p) -> (valid_triple (Flet id t (msubst p x id))
  (Sassign x t) p).

Axiom seq_rule : forall (p:fmla) (q:fmla) (r:fmla) (s1:stmt) (s2:stmt),
  ((valid_triple p s1 r) /\ (valid_triple r s2 q)) -> (valid_triple p
  (Sseq s1 s2) q).

Axiom if_rule : forall (t:term) (p:fmla) (q:fmla) (s1:stmt) (s2:stmt),
  ((valid_triple (Fand p (Fterm t)) s1 q) /\ (valid_triple (Fand p
  (Fnot (Fterm t))) s2 q)) -> (valid_triple p (Sif t s1 s2) q).

Axiom assert_rule : forall (f:fmla) (p:fmla), (valid_fmla (Fimplies p f)) ->
  (valid_triple p (Sassert f) p).

Require Import Why3.
Ltac ae := why3 "alt-ergo" timelimit 3.

(* Why3 goal *)
Theorem assert_rule_ext : forall (f:fmla) (p:fmla), (valid_triple (Fimplies f
  p) (Sassert f) p).
unfold valid_triple.
intros f p.
intros.
inversion H0; subst; clear H0.
simpl in H.
inversion H1; subst; clear H1.
inversion H2; subst; clear H2; auto.
inversion H0.
581
Qed.